Towards a Political Economy of Tobacco Control in Low- and Middle-Income Countries - Bump, J.B.; Reich, M.R.; Adeyi, O.; Khetrapal, S. (World Bank, Washington, DC, 2013)
This study provides the basis for constructing a political economy of tobacco control in low- and middle-income countries (LMICs). The authors first undertook a literature review of tobacco control in LMICs to explore the forces that oppose the adoption, implementation, and enforcement of tobacco control strategies. The authors then used the sources collected to conduct a stakeholder analysis, as a first step in constructing a political economy of tobacco control in LMICs. The authors focused primarily at the international level because of the dominant role of transnational tobacco companies (TTCs). The author's review of the literature suggests four broad conclusions. First, a political economy approach has been applied only rarely as a formal analytical methodology in the literature on the tobacco control in LMICs. Second, even when the term "political economy" was used in a document, the paper typically did not explicitly conduct this kind of analysis and did not directly consider political strategies for advancing tobacco control. Third, translating the framework convention on tobacco control into tobacco use reductions at the national level is likely to require national-level political economy analyses to define political strategies appropriate to the particular national setting. Fourth, tobacco control's present and past is well documented, but analyses of future scenarios have focused on projections of health consequences and smoking trends. How TTCs will try to grow in the future has not been adequately addressed in the literature.